e-learning in higher institutions and secondary schools during Covid-19: Crisis solving and future perspectives - Mateja Brozović; Marina Ercegović; Gunther Meeh-Bunse (Business Systems Research (BSR), 2022)
Background: The pandemic of Covid-19 brought significant changes to the education system and forcibly accelerated the process of digitizing teaching. Students and educators had to adapt to the new way of education, facing challenges such as technical problems and a lack of technical skills and social contact. Objectives: The purpose of the paper was to explore the attitudes of the university and high school educators and students towards the pandemic's impact on digitization in teaching. Methods/Approach: Data were collected through a questionnaire distributed to university and high school educators and students in Croatia, Poland, Serbia and Germany in the field of accounting, finance, trade, tourism, and other areas of interest, resulting in 2,897 responses. The results were analyzed using descriptive statistics and non-parametric tests. Results: The research showed that: 1) high school students were less optimistic about the positive impact of the pandemic on applying digital tools in teaching than university students, 2) educators generally prefer traditional exams, while students generally prefer e-exams, 3) a higher proportion of university respondents believe that e-learning should be used as an important addition to traditional teaching when compared to high school respondents. Conclusions: The pandemic has changed how the teaching process will be performed, but we should learn from experience and address the issues with e-learning.
Keywords: A20; I21; I23; 033; 330; e-learning; digital tools; Covid-19 pandemic; e-exams; university; high school